Treatment of T-Cell Prolymphocytic Leukemia with Central Nervous System Involvement Using Intrathecal Alemtuzumab Administration - Jinichi Mori; Kumi Oshima; Satoshi Kimura; Takayuki Ikezoe (Case Reports in Hematology)
T-cell prolymphocytic leukemia (T-PLL) is a rare hematologic cancer with a dismal prognosis. Although a small number of patients have central nervous system (CNS) involvement, a standard treatment approach for these patients has not been established. Herein, we present a case of T-PLL with CNS involvement that was treated with a higher dose of intrathecal alemtuzumab than that previously reported. A 66-year-old man who had T-PLL with CNS involvement was admitted to our hospital. Intravenously administered alemtuzumab, a monoclonal antibody against the CD52 antigen, successfully reduced leukemia cells in peripheral blood; however, intrathecal treatment with methotrexate, cytarabine, and prednisone had a limited effect on the CNS involvement. Therefore, we intrathecally injected alemtuzumab as an experimental treatment. Although we escalated the dose of intrathecal alemtuzumab up to 5 mg, no adverse reaction was noted; however, this treatment did not completely clear the leukemia cells from the patient’s cerebrospinal fluid (CSF). We performed whole brain and whole spinal irradiation therapies and subsequently performed allogeneic transplantation from a human leukocyte antigen-matched sibling donor with a conditioning regimen containing total body irradiation. At 21 days after transplantation, leukemia cells remained in his CSF. Although intrathecal alemtuzumab did not eliminate the CNS-invading leukemia cells, it was well-tolerated in our case. Further accumulation of similar cases is needed to determine the benefits and safety of intrathecal alemtuzumab administration.